ANALISIS PENERAPAN AKUNTANSI PADA USAHA EKONOMI DESA SIMPAN PINJAM (UED-SP) PERMAI DESA SUNGAI CINGAM KECAMATAN RUPAT KABUPATEN BENGKALIS - Hazima Hazima; Rosmida Rosmida; Wan Junita Raflah (Politeknik Negeri Bengkalis, 2016)
Abstract: This research was conducted in UED-SP Permai Sungai Cingam Rupat, District of Bengkalis. The purpose of this study was to determine whether the accounting has been applied in UED-SP Permai Sungai Cingam Rupat, District of Bengkalis in accordance with the Generally Accepted Accounting Principles (GAAP). Data of study consisted of primary and secondary data. Based on the research and discussion conducted found some problems such as is not classify assets into current assets and fixed assets, does not classify debts into long-term debt and short-term debt and in calculating the inventory usage is not in accordance with the service life should be. In the process of implementation of the financial statements UED-SP Permai Sungai Cingam Rupat, District of Bengkalis is not follow all the Accounting Cycle, UED-SP Permai is not present Statement of Changes in Equity, Statement of Cash Flow, and Notes to Financial Statements. The results of research conducted on Usaha Ekonomi Desa-Simpan Pinjam (UED-SP) Permai can be concluded that the accounting is not applied on the whole in accordance with the Generally Accepted Accounting Principles (GAAP). Keywords: Financial Statements, UED-SP Sungai Cingam